Usage of Almond and Thyme Oils for the Enhancement of Shelf Life of Different Fish Species - Kanwal, Aneeza; Yasmeen, Roheela; Nazir, Saima; Usman, Shumaila; Khan, Bushra Nisar (CORE Scholar, 2024)
Fish is an important source of protein for millions of people around the globe and it's often a healthier option compared to some other meats. However, the fish industry is facing a storage challenge in the form of rapid spoilage and deterioration of freshness due to bacterial growth and enzymatic activity. The usage of oils in fish can enhance shelf life by creating a protective barrier. This research was designed to see the effects of thyme and almond oil on nutritional profile and shelf life of fish. The three fish species rohu (Labeo rohita), Mali (Wallago attu) and Dola (Channa punctata) were used. Two 15 % and 25 % nano-emulsions of almond and thyme oils were prepared, coated on fish meat samples (3-5 cm) and kept for twenty-one days in refrigerator at 4℃. A proximate analysis such as determination of moisture, ash, protein, and fat contents of storage samples were carried out at 7th and 21st days. It was noticed that ash, protein, and fat contents increased with increasing storage period while there was no changes noticed in pH of samples with increasing period. It was observed that control sample (without oils) contained lowest ash, protein and fat contents and highest moisture contents. A statistical analysis was carried out by one way ANOVA and significant differences were noticed among the control and oil coated samples at value < 0.05. The results showed L. rohita contained highest protein (15.43 ± 0.39) and fat contents (3.78 ± 1.00) at 25 % nano-emulsion of thyme while W. attu contained highest fat (3.70±1.03) and ash content (2.86 ± 0.56) at 25 % thyme. A high pH was noticed in C. punctata as compared to other experimental fish species. It was concluded fish quality enhanced under storage period with oil coated samples particularly with 25 % nano-emulsion of thyme oil.